On the relevance of chaos for halo stars in the solar neighbourhood II - Maffione, Nicolás Pablo (2018)
Fil: Maffione, Nicolás P. Universidad Nacional de Río Negro. Sede Antina. Laboratorio de Procesamiento de Señales Aplicadas y Computación de Alto Rendimiento; Argentina.